Skin tumors and skin infections in kidney transplant recipients vs. patients with pemphigus vulgaris. (22nd August 2013) - Sharquie, Khalifa E.; Noaimi, Adil A.; Al‐Jobori, Ali A.
Abstract Background Pemphigus vulgaris is an autoimmune disease of the skin and mucous membrane. Renal transplantation is a common procedure in Iraq, and these patients required prolonged use of immunosuppressive drugs. Objective To study the frequency of skin tumors and infections in patients with pemphigus vulgaris compared with renal transplant recipients and normal controls. Patients and methods One hundred kidney transplant recipients, their ages ranged from 14 to 70 (46.65 ± 4.74) years, and 50 patients with pemphigus vulgaris, their ages ranged from 22 to 70 (43.32 ± 3.46) years, were studied in Baghdad Hospital from June 2009 to August 2010. Patients were treated with immunosuppressive drugs for 0.5–25 years. Patients were examined for tumors and infections and compared with the general population as controls (100 individuals). Results In renal transplant recipients, the following infections were observed: herpetic, 25 patients (25%); bacterial, 11 (11%); and fungal, 22 (22%). These infections appeared early in the course of immunosuppression. Benign tumors increased, most importantly viral warts in 40 (40%) and actinic keratosis, 14 (14%). The malignant tumors were basal cell carcinomas in 4 (4%), squamous cell carcinomas 2 (2%), and Kaposi's sarcoma 3 (3%). These malignancies usually appeared late in the course of immunosuppression. Patients with pemphigus vulgaris showed no important skin infections or tumors. Healthy controls showed no infections apart from herpetic infections in 7 (7%) and viral warts in 9 (9%). No tumors were seen. Conclusions Pemphigus vulgaris in prolonged immunosuppression is immunoprotective against skin infections and skin tumors while kidney transplant recipients are not protective.